Carbon material, composite material, phenol resin for carbon material, resin composition, method for producing composite material, lithium ion battery negative electrode, and lithium ion battery
By controlling the orthogonalization rate and other physical indicators of the carbide phenolic resin, high-performance carbon materials are prepared and negative electrode active materials used in lithium-ion batteries are solved, and the discharge capacity and stability are improved.
Patent Information
- Application Number
- JP2023120502
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
The prior art is difficult to increase the discharge capacity of lithium-ion batteries.
Carbonated phenolic resin within a specific numerical range is used as the negative electrode active material. By controlling its orthogonalization rate, specific surface area, peak intensity ratio, true density, hygroscopy rate and Raman spectrum ratio, high-performance carbon materials are prepared and composited with other materials to form composite materials as the negative electrode active material.
It significantly improves the discharge capacity and stability of lithium-ion batteries, reduces hygroscopicity, and improves the overall performance of the battery.
Smart Images

Figure 2025017465000002 
Figure 2025017465000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon material, a composite material, a phenolic resin for a carbon material, a resin composition, a method for producing a composite material, a negative electrode for a lithium ion battery, and a lithium ion battery. [Background technology]
[0002] Carbon materials obtained by carbonizing phenolic resins have been studied as negative electrode active materials for lithium ion batteries. Patent Document 1, for example, describes a technique related to such carbon materials.
[0003] Patent Document 1 describes a lithium ion secondary battery having a large charge / discharge capacity as an objective of the present invention, and is characterized in that the battery uses, as the negative electrode, carbon obtained by heat-treating amino resin-modified resol-type phenolic resin (a) obtained by mixing and / or reacting a resol-type phenolic resin with an amino resin, and / or amino-modified resol-type phenolic resin (b) obtained by reacting a phenol, an amino compound, and formaldehyde in the presence of an alkaline catalyst. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2002-075357 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention provides a carbon material that can realize a lithium ion battery with improved discharge capacity. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to achieve the above object, and have found that the discharge capacity of a lithium ion battery can be improved by using a carbonized material obtained by carbonizing a phenolic resin having an ortho ratio within a specific range as a negative electrode active material, thereby completing the present invention.
[0007] According to the present invention, there are provided a carbon material, a composite material, a phenolic resin for a carbon material, a resin composition, a method for producing a composite material, a negative electrode for a lithium ion battery, and a lithium ion battery, which are shown below. [1] A carbon material (A) that can be used as a negative electrode active material for a lithium ion battery, The carbon material (A) is a carbon material containing a carbonized product of a phenolic resin having an ortho-conversion rate of 50% or more. [2] BET specific surface area is 0.1m 2 / g or more 50m 2 / g or less. [3] The carbon material according to the above [1] or [2], wherein in an X-ray diffraction spectrum measured by an X-ray diffraction (XRD) method, a peak intensity ratio measured by the following method 1 is 0.90 or more and 1.25 or less. Method 1: In an X-ray diffraction spectrum obtained by measurement using CuKα radiation as a radiation source at a scanning speed of 1° / min, with 2θ on the horizontal axis and diffraction intensity on the vertical axis, the peak intensities at 2θ values of 15°, 24°, and 35° are Ia, Ib, and Ic, respectively, and the peak intensity ratio is calculated as (Ia-Ic) / (Ib-Ic). [4] True specific gravity is 1.50g / cm 3 More than 3.00g / cm 3 The carbon material according to any one of the above [1] to [3], which is: [5] The carbon material according to any one of the above [1] to [4], which has a moisture absorption rate of 5.0% or more and 15.0% or less, as measured by the following method 2. Method 2: 1 g of the carbon material is left for 1 hour under the conditions of a temperature of 40° C. and a humidity of 95% RH. The moisture absorption rate (%) is calculated from the change in mass of the carbon material before and after leaving it, using the following formula (3). Moisture absorption rate (%) = (mass of carbon material after standing - mass of carbon material before standing) / (mass of carbon material before standing) x 100 (3) [6] The carbon material according to any one of the above [1] to [5], which has an R value of 0.5 or more and 1.5 or less in Raman spectroscopy measured by the following method 3. Method 3: Using a micro-Raman spectrometer, the Raman spectrum of the carbon material is measured under the following conditions. -1 Peak intensity near 1360 ) and 1580cm -1 Peak intensity near 1580 ) intensity ratio (R value, R=I 1360 / I 1580 ) is calculated. Laser wavelength: 532nm Measurement range: 400cm -1 ~2000cm -1 Number of times: 4 [7] A composite material comprising the carbon material (A) according to any one of the above [1] to [6]. [8] The composite material according to [7] above, further comprising a negative electrode active material (B) different from the carbon material (A). [9] The composite material according to [8] above, wherein the negative electrode active material (B) contains a carbon material (B1) different from the carbon material (A).
[10] The composite material according to the above-mentioned [9], wherein the carbon material (B1) comprises one or more selected from the group consisting of graphite, hard carbon and soft carbon.
[11] The composite material according to the above [8], wherein the negative electrode active material (B) contains one or more metal materials (B2) selected from the group consisting of metals and metal oxides.
[12] The composite material according to
[11] above, wherein the metal material (B2) comprises one or more elements selected from the group consisting of copper, gold, platinum, titanium, iron, cobalt, nickel, zinc, chromium, molybdenum, tungsten, palladium, calcium, strontium, barium, iridium, silver, cadmium, mercury, boron, aluminum, gallium, indium, thallium, silicon, tin, lead, antimony, bismuth and tellurium, and oxides thereof.
[13] A phenolic resin for a carbon material capable of forming the carbon material according to any one of the above [1] to [6], The phenolic resin for carbon materials has an ortho-conversion rate of 50% or more.
[14] The phenolic resin for carbon materials according to the above
[13] , wherein the zinc content in 100% by mass of the phenolic resin for carbon materials is 0.1% by mass or more and 2.0% by mass or less.
[15] The phenolic resin for carbon materials according to the above
[13] or
[14] , wherein the phenolic resin for carbon materials contains a thermoplastic phenolic resin.
[16] The thermoplastic phenolic resin comprises one or more selected from the group consisting of novolac-type phenolic resins and modified novolac-type phenolic resins.
[17] A resin composition comprising the phenolic resin for carbon materials according to any one of the above
[13] to
[16] , and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B).
[18] A step of preparing a resin composition containing the phenolic resin for carbon materials according to any one of the above
[13] to
[16] and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B); A step of carbonizing the resin composition; A method for producing a composite material, comprising:
[19] A negative electrode for a lithium ion battery, comprising the carbon material according to any one of the above [1] to [6].
[20] A lithium ion battery comprising the lithium ion battery negative electrode according to
[19] above. Effect of the Invention
[0008] According to the present invention, a carbon material capable of realizing a lithium ion battery with improved discharge capacity can be provided. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a lithium ion battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5% by mass" means "from 1% by mass to 5% by mass". In this specification, the term "solid content" refers to the entire components from which volatile components such as water and organic solvents have been removed. For example, even if a component is in the form of a liquid at room temperature, the component that does not volatilize is counted as being a solid content.
[0011] <Carbon materials> The carbon material of the present embodiment is a carbon material (A) that can be used as a negative electrode active material for a lithium ion battery, and the carbon material (A) contains a carbonized material of a phenol resin having an ortho ratio of 50% or more. This can improve the discharge capacity of a lithium ion battery using the carbon material (A) of the present embodiment.
[0012] A carbon material obtained by carbonizing a phenolic resin having an ortho ratio of 50% or more has the characteristics of a high carbonization yield, a low specific surface area, and a low degree of crystallinity. In the case of a phenolic resin having a high ortho ratio, hydrogen bonding is generally likely to occur between adjacent hydroxyl groups in the molecule, and the volatilization of low-molecular components in the phenolic resin during carbonization is suppressed, improving the carbonization yield. In addition, the volatilization of water vapor gas accompanying the dehydration reaction of adjacent hydroxyl groups occurs at the beginning of carbonization, and the carbonization progresses thereafter, causing the pores to shrink and the specific surface area to decrease. Due to these characteristics, it is believed that the carbon material of this embodiment can improve the discharge capacity when used in a lithium-ion battery. The phenolic resin from which such a carbon material can be obtained will be described later.
[0013] The lower limit of the ortho ratio of the phenolic resin in the carbon material (A) of this embodiment is 50% or more, preferably 55% or more, more preferably 60% or more, even more preferably 65% or more, and even more preferably 68% or more. When the ortho ratio of the phenolic resin is equal to or more than the lower limit, the discharge capacity of the lithium ion battery using the carbon material of this embodiment can be improved. In addition, the upper limit of the ortho ratio of the phenol resin of this embodiment is not particularly limited, but is, for example, 100% or less, 90% or less, 80% or less, 75% or less, or 70% or less.
[0014] In this case, the orthorectification rate is, for example, 13 It can be measured by using C-NMR spectroscopy. Specifically, the ortho conversion rate of phenolic resin is 13 The methylene group binding amount determined by C-NMR spectroscopy is substituted into the following formula (1) to calculate. Ortho ratio = (X+Y / 2) / (X+Y+Z) × 100(%) (1) X: Number of methylene groups bonded to the ortho-ortho positions of the phenol nucleus Y: The number of methylene groups bonded to the ortho- and para-positions of the phenol nucleus Z: Number of methylene groups bonded to the para-para positions of the phenol nucleus For the NMR measurement, for example, a JNM-AL300 manufactured by JEOL Datum Co., Ltd. is used, and the measurement conditions are such that the number of integration times is, for example, 10,000.
[0015] The lower limit of the BET specific surface area of the carbon material (A) in this embodiment is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1.0m 2 / g or more, more preferably 3.0m 2 / g or more, more preferably 5.0m 2 When the BET specific surface area of the carbon material (A) is equal to or more than the above lower limit, the discharge capacity of the lithium ion battery using the carbon material (A) of the present embodiment can be further improved. The upper limit of the BET specific surface area of the carbon material (A) in this embodiment is preferably 50 m 2 / g or less, more preferably 40m 2 / g or less, more preferably 30m 2 / g or less, more preferably 20m 2 / g or less, more preferably 15m 2 When the BET specific surface area of the carbon material (A) is equal to or less than the upper limit, the moisture absorption resistance of the carbon material (A) of the present embodiment can be improved, and as a result, the discharge capacity of a lithium ion battery using the carbon material (A) of the present embodiment can be further improved.
[0016] At this time, the BET specific surface area of the carbon material (A) of the present embodiment can be measured, for example, by a nitrogen adsorption method. Specific examples of the method for measuring the BET specific surface area include the following methods. First, the carbon material (A) pre-dried at 100°C is placed in a glass cell and degassed under vacuum at 350°C for 5 hours. Next, nitrogen gas is introduced little by little at a temperature of 77K, and the equilibrium pressure and adsorption amount are measured. The measurement results are analyzed using the BET equation (equation (2) below) to determine the BET specific surface area (m 2 / g) is calculated. P / V(P0-P)=1 / V m C+(C-1 / V m C)(P / P0) (2) Here, P is the adsorption equilibrium pressure, V is the amount of nitrogen gas adsorbed at the adsorption equilibrium pressure, P0 is the saturated vapor pressure, and V m indicates the amount of monolayer adsorption, and C indicates the heat of adsorption parameter. Such measurement and analysis of the BET specific surface area by the nitrogen adsorption method can be performed using, for example, a commercially available adsorption measurement device, BELSORP-MAX II manufactured by Microtrack-Bell Corporation.
[0017] In the carbon material (A) of this embodiment, the lower limit of the peak intensity ratio in the X-ray diffraction spectrum measured by the X-ray diffraction (XRD) method is preferably 0.90 or more, more preferably 0.91 or more, even more preferably 0.92 or more, even more preferably 0.93 or more, and even more preferably 0.94 or more. When the peak intensity ratio of the carbon material (A) is the above-mentioned lower limit or more, the discharge capacity can be further improved in the lithium ion battery using the carbon material (A) of this embodiment. The upper limit of the peak intensity ratio is preferably 1.25 or less, more preferably 1.20 or less, even more preferably 1.15 or less, even more preferably 1.10 or less, even more preferably 1.05 or less, even more preferably 1.00 or less, even more preferably 0.97 or less, even more preferably 0.96 or less. By having the peak intensity ratio of the carbon material (A) be the upper limit or less, the discharge capacity can be further improved in the lithium ion battery using the carbon material (A) of the present embodiment.
[0018] In this case, the peak intensity ratio in the X-ray diffraction spectrum measured by the X-ray diffraction (XRD) method in the carbon material (A) of the present embodiment can be measured by the following method 1. Method 1: In an X-ray diffraction spectrum obtained by measurement using CuKα radiation as a radiation source at a scanning speed of 1° / min, with 2θ on the horizontal axis and diffraction intensity on the vertical axis, the peak intensities at 2θ values of 15°, 24°, and 35° are Ia, Ib, and Ic, respectively, and the peak intensity ratio is calculated as (Ia-Ic) / (Ib-Ic).
[0019] The lower limit of the true specific gravity of the carbon material (A) in this embodiment is preferably 1.50 g / cm 3 More preferably, 1.60 g / cm 3 More preferably, 1.70 g / cm 3 More preferably, 1.80 g / cm 3 More preferably, 1.90 g / cm 3 More preferably, 2.00 g / cm 3 More preferably, 2.10 g / cm 3 More preferably, 2.20 g / cm 3 By making the true specific gravity of the carbon material (A) equal to or more than the above lower limit, the discharge capacity of the lithium ion battery using the carbon material (A) of the present embodiment can be further improved. The upper limit of the true specific gravity of the carbon material (A) in this embodiment is preferably 3.00 g / cm 3 Less than or equal to 2.90 g / cm 3 More preferably, 2.80 g / cm 3 More preferably, 2.70 g / cm 3 More preferably, 2.60 g / cm 3 More preferably, 2.50 g / cm 3 More preferably, 2.40 g / cm 3 More preferably, 2.30 g / cm 3 When the true specific gravity of the carbon material (A) is equal to or less than the above upper limit, the discharge capacity of the lithium ion battery using the carbon material (A) of the present embodiment can be further improved. At this time, the true specific gravity of the carbon material (A) of the present embodiment is specifically measured by a dry-type automatic densimeter, such as Accupyc II1340 (manufactured by Shimadzu Corporation).
[0020] The lower limit of the moisture absorption rate of the carbon material (A) of this embodiment is preferably 5.0% or more, more preferably 6.0% or more, even more preferably 7.0% or more, and even more preferably 8.0% or more. When the moisture absorption rate of the carbon material (A) is the above-mentioned lower limit or more, the discharge capacity can be further improved in the lithium ion battery using the carbon material (A) of this embodiment. The upper limit of the moisture absorption rate of the carbon material (A) of this embodiment is preferably 15.0% or less, more preferably 12.5% or less, even more preferably 12.0% or less, even more preferably 11.0% or less, even more preferably 10.0% or less, and even more preferably 9.0% or less. By making the moisture absorption rate of the carbon material (A) equal to or less than the above upper limit, the discharge capacity of the lithium ion battery using the carbon material (A) of this embodiment can be further improved.
[0021] In this case, the moisture absorption rate of the carbon material (A) of the present embodiment can be measured by the following method 2. Method 2: 1 g of carbon material (A) is left for 1 hour under the conditions of temperature 40°C / humidity 95%RH. The moisture absorption rate (%) is calculated from the change in mass of the carbon material before and after leaving it, using the following formula (3). Moisture absorption rate (%) = (mass of carbon material after standing - mass of carbon material before standing) / (mass of carbon material before standing) x 100 (3)
[0022] In the carbon material (A) of this embodiment, the lower limit of the R value indicating the intensity ratio of the Raman spectrum is preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, and even more preferably 0.8 or more. When the R value of the carbon material (A) is the above-mentioned lower limit or more, the discharge capacity can be further improved in the lithium ion battery using the carbon material (A) of this embodiment. The upper limit of the R value of the carbon material (A) of this embodiment is preferably 1.5 or less, more preferably 1.4 or less, even more preferably 1.3 or less, even more preferably 1.2 or less, even more preferably 1.1 or less, even more preferably 1.0 or less, and even more preferably 0.9 or less. By making the R value of the carbon material (A) equal to or less than the upper limit, the orientation of the carbon material (A) of this embodiment can be controlled, and a well-balanced reduction in moisture absorption and an improvement in discharge capacity can be achieved without increasing costs.
[0023] In this case, the R value of the carbon material (A) of the present embodiment can be measured by the following method 3. Method 3: The Raman spectrum of the carbon material (A) is measured using a micro-Raman spectrometer under the following conditions. -1 Peak intensity near 1360 ) and 1580cm -1 Peak intensity near 1580 ) intensity ratio (R value, R=I 1360 / I 1580 ) is calculated. Laser wavelength: 532nm Measurement range: 400cm -1 ~2000cm -1 Number of times: 4
[0024] In this case, the microscopic Raman spectroscopic device may be, for example, an InViaReflex Raman Microscope (manufactured by RENISHAW).
[0025] Such a carbon material (A) can be obtained by carbonizing a phenolic resin for carbon materials, which will be described later. The method for carbonizing the phenolic resin for carbon material is preferably a method using equipment capable of heat treatment under an inert gas atmosphere, and known gases such as nitrogen, helium, and argon can be used as the inert gas.
[0026] The equipment capable of performing heat treatment that can be used when carbonizing the phenolic resin for carbon material is not particularly limited, and any known equipment can be selected, such as a rotary kiln, a vertical shaft kiln, a batch-type heating furnace, a roller hearth kiln, a spray pyrolysis device, a spray dryer, etc. The above-mentioned equipment can be used alone or in combination of two or more types depending on the properties required for the carbon material (A) and the production efficiency of the carbon material (A).
[0027] The heating temperature when carbonizing the phenolic resin for carbon materials may be appropriately set within the range of preferably 400 to 1500° C., more preferably 450 to 1450° C., further preferably 500 to 1400° C., and further preferably 550 to 1300° C. The carbonization of the phenolic resin for carbon materials may be carried out in a reducing atmosphere such as argon, nitrogen, or carbon dioxide.
[0028] In this embodiment, it is preferable to repeat the carbonization of the phenolic resin for carbon material multiple times, which allows the physical properties of the obtained carbon material to be controlled. Furthermore, it is preferable to include at least one step of pulverizing the carbonized material obtained in the previous step between multiple carbonizations of the phenolic resin for carbon material. Furthermore, the maximum carbonization temperature in the final carbonization of the phenolic resin for carbon material is preferably 400 to 1500°C, more preferably 600 to 1450°C, further preferably 800 to 1400°C, and further preferably 1000 to 1300°C.
[0029] In this embodiment, the time for holding the maximum carbonization temperature when carbonizing the phenolic resin for carbon material (hereinafter referred to as the "holding time") is preferably 0 to 24 hours, more preferably 0 to 18 hours, even more preferably 0 to 12 hours, even more preferably 0.5 to 6 hours, even more preferably 1.0 to 4 hours, and even more preferably 1.5 to 2 hours, from the viewpoints of controlling the mechanical properties of the obtained carbon material (A) and improving the discharge capacity of a lithium ion battery using the obtained carbon material (A).
[0030] For example, when carbonizing a phenolic resin for a carbon material in two steps, the primary carbonization can be performed at a temperature of 150 to 700°C, and the carbon material can then be further treated at a temperature of 800°C or higher (secondary carbonization).
[0031] The lower limit of the carbonization yield of the carbon material (A) of this embodiment is preferably 35% or more, more preferably 40% or more, even more preferably 45% or more, and even more preferably 46% or more. By having the carbonization yield of the carbon material (A) be equal to or more than the above lower limit, the production efficiency of the carbon material (A) of this embodiment can be improved, and the mechanical properties such as bending strength, compressive strength, friction characteristics, and hardness of a composite material containing the carbon material (A) of this embodiment can be improved. In addition, the upper limit of the carbonization yield of the carbon material (A) of this embodiment is not particularly limited, and is, for example, 100% or less, 90% or less, 80% or less, 70% or less, 60% or less, or 50% or less. At this time, the carbonization yield can be calculated from the following formula (4). Carbonization yield (%) = {mass after carbonization / mass before carbonization} × 100 (4)
[0032] <Composite materials> The composite material of the present embodiment preferably contains the carbon material (A), which can further improve the discharge capacity of a lithium ion battery using the composite material of the present embodiment.
[0033] The composite material of the present embodiment preferably contains, in addition to the carbon material (A), a negative electrode active material (B) different from the carbon material (A), which can further improve the discharge capacity of a lithium ion battery using the composite material of the present embodiment. As such a negative electrode active material (B), any known material that can be used as a negative electrode active material can be used. However, in a lithium ion battery using the composite material of the present embodiment, from the viewpoint of further improving the discharge capacity, it is preferable that the negative electrode active material (B) contains a carbon material (B1) different from the carbon material (A), or one or more metal materials (B2) selected from the group consisting of metals and metal oxides.
[0034] In this embodiment, the content of the negative electrode active material (B) is preferably 1 mass % or more, more preferably 5 mass % or more, even more preferably 10 mass % or more, even more preferably 20 mass % or more, and even more preferably 40 mass % or more, when the entire composite material is taken as 100 mass %. In addition, the content of the negative electrode active material (B) in this embodiment is preferably 99 mass % or less, more preferably 98 mass % or less, and further preferably 95 mass % or less, when the entire composite material is taken as 100 mass %.
[0035] The form in which the carbon material (A) of the present embodiment is adhered to the negative electrode active material (B) of the present embodiment is not particularly limited. For example, the carbon material (A) may be adhered to the surface of the negative electrode active material (B) in the form of a film, or the carbon material (A) may be adhered to the surface of the negative electrode active material (B) in the form of islands.
[0036] [Carbon material (B1)] The carbon material (B1) in the composite material of the present embodiment preferably contains one or more selected from the group consisting of graphite, hard carbon and soft carbon, which can further improve the discharge capacity of the lithium ion battery using the composite material of the present embodiment.
[0037] (graphite) Graphite is a carbon allotrope and a hexagonal, plate-like crystalline material with a layered lattice made up of linked layers of six carbon rings.
[0038] When graphite is used in lithium-ion batteries, the charge / discharge capacity decreases quickly after repeated cycling. Although lithium-ion secondary batteries using graphite have poor input / output characteristics at large currents, they have the advantage of excellent charge / discharge efficiency. Therefore, by containing graphite in addition to the carbon material (A) in the composite material of the present embodiment, in a lithium ion battery using the composite material of the present embodiment, it is possible to improve the charge / discharge efficiency while improving the stability during cycles and the large current input / output characteristics.
[0039] (Hard carbon, soft carbon) Hard carbon and soft carbon refer to amorphous carbon obtained by carbonizing raw resin or raw resin composition. Among them, hard carbon refers to carbon that is difficult to graphitize, for example, a carbon material that is difficult to generate graphite even when heated in an inert atmosphere. Soft carbon refers to a carbon material that is easily changed to a highly crystalline graphite structure by high-temperature treatment. Hard carbon and soft carbon are amorphous, and therefore have high stability during cycling, making it easy to input and output a large current.
[0040] Such hard carbon and soft carbon are preferably obtained by carbonizing a raw resin or a raw resin composition. By carbonizing, the raw resin or the raw resin composition is carbonized and can be used as a carbon material for lithium ion batteries. The raw resin or the raw resin composition that is the raw material for hard carbon and soft carbon is not particularly limited, and examples thereof include thermosetting resins; thermoplastic resins; petroleum-based or coal-based tar or pitch such as petroleum-based tar or pitch by-produced during ethylene production, coal tar produced during coal dry distillation, heavy components or pitch obtained by distilling off low boiling point components of coal tar, and tar or pitch obtained by liquefying coal; and further, the above tar or pitch is crosslinked; and the like. One or more of these can be used in combination.
[0041] As described later, the raw material resin composition contains the above resin as a main component and may also contain a curing agent, additives, etc., and may further be appropriately subjected to a crosslinking treatment such as oxidation.
[0042] The thermosetting resin is not particularly limited, and examples thereof include some phenolic resins such as resol-type phenolic resins, epoxy resins such as bisphenol-type epoxy resins and novolac-type epoxy resins, melamine resins, urea resins, aniline resins, cyanate resins, furan resins, ketone resins, unsaturated polyester resins, urethane resins, etc. Modified products of these resins modified with various components can also be used.
[0043] Furthermore, the thermoplastic resin is not particularly limited, and examples thereof include some phenolic resins such as novolac-type phenolic resins; polyethylene, polystyrene, polyacrylonitrile, acrylonitrile-styrene (AS) resin, acrylonitrile-butadiene-styrene (ABS) resin, polypropylene, vinyl chloride, methacrylic resin, polyethylene terephthalate, polyamide, polycarbonate, polyacetal, polyphenylene ether, polybutylene terephthalate, polyphenylene sulfide, polysulfone, polyethersulfone, polyetheretherketone, polyetherimide, polyamideimide, polyimide, and polyphthalamide.
[0044] Among these, it is preferable to use a resin selected from novolac-type phenolic resin, resol-type phenolic resin, melamine resin, furan resin, aniline resin, and modified products thereof. This allows greater freedom in designing the composite material, and allows it to be manufactured at low cost. In addition, the discharge capacity of a lithium ion battery using the composite material of this embodiment can be further improved.
[0045] The raw resin composition of the present embodiment may also contain a curing agent. The curing agent used is not particularly limited, and for example, in the case of a novolac type phenolic resin, hexamethylenetetramine, a resol type phenolic resin, polyacetal, paraformaldehyde, etc. can be used. In addition, in the case of an epoxy resin, a curing agent known for epoxy resins can be used, such as a polyamine compound such as an aliphatic polyamine or an aromatic polyamine, an acid anhydride, an imidazole compound, dicyandiamide, a novolac type phenolic resin, a bisphenol type phenolic resin, or a resol type phenolic resin.
[0046] In addition, even if a raw material resin is normally used in combination with a specified amount of a curing agent, it may be used in a smaller amount than usual or without the use of a curing agent in the raw material resin composition of this embodiment.
[0047] In addition to the above components, additives may be added to the raw material resin composition. The additives used here are not particularly limited, but examples thereof include carbon material precursors carbonized at 200 to 800° C., organic acids, inorganic acids, nitrogen-containing compounds, oxygen-containing compounds, aromatic compounds, non-ferrous metal elements, etc. These additives can be used alone or in combination of two or more depending on the type and properties of the resin used.
[0048] [Metal material (B2)] The metal material (B2) in the composite material of this embodiment preferably contains one or more selected from the group consisting of copper, gold, platinum, titanium, iron, cobalt, nickel, zinc, chromium, molybdenum, tungsten, palladium, calcium, strontium, barium, iridium, silver, cadmium, mercury, boron, aluminum, gallium, indium, thallium, silicon, tin, lead, antimony, bismuth, and tellurium, and oxides thereof. This can further improve the discharge capacity of the lithium ion battery using the composite material of this embodiment.
[0049] <Phenol resin for carbon materials> The phenolic resin for carbonaceous materials of the present embodiment is a phenolic resin for carbonaceous materials capable of forming the above-mentioned carbonaceous material (A), and the phenolic resin for carbonaceous materials has an ortho-conversion rate of 50% or more. This makes it possible to provide a carbonaceous material capable of realizing a lithium ion battery with improved discharge capacity.
[0050] The lower limit of the ortho-conversion rate of the phenolic resin for carbon materials of the present embodiment is 50% or more, preferably 55% or more, more preferably 60% or more, even more preferably 65% or more, and even more preferably 68% or more. By making the ortho-conversion rate of the phenolic resin for carbon materials equal to or more than the above lower limit, it is possible to provide a carbon material that can realize a lithium ion battery with improved discharge capacity. In addition, the upper limit of the ortho ratio of the phenolic resin for carbon materials of this embodiment is not particularly limited, but is, for example, 100% or less, 90% or less, 80% or less, 75% or less, or 70% or less. In this case, the ortho-conversion rate of the phenolic resin for carbon material can be measured by the above-mentioned method.
[0051] As the phenolic resin for the carbon material of the present embodiment, a known phenolic resin can be used. Examples of the known phenolic resin include a novolac type phenolic resin, a modified novolac type phenolic resin, a resol type phenolic resin, and a modified resol type phenolic resin. Among these, the phenolic resin for carbon material of the present embodiment preferably contains a thermoplastic phenolic resin, which makes it possible to provide a carbon material capable of realizing a lithium ion battery having a further improved discharge capacity. The thermoplastic phenolic resin preferably contains one or more selected from the group consisting of novolac phenolic resins and modified novolac phenolic resins, thereby providing a carbon material capable of realizing a lithium ion battery with a further improved discharge capacity.
[0052] The phenolic resin for carbon material of the present embodiment preferably contains zinc, which not only provides a carbon material capable of realizing a lithium ion battery with improved discharge capacity, but also allows the orientation of the carbon material to be controlled and reduces the hygroscopicity without increasing costs. In the phenolic resin for carbon materials of this embodiment, the lower limit of the zinc content in 100% by mass of the phenolic resin for carbon materials is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more. By having the zinc content be equal to or more than the lower limit, the orientation of the carbon material can be controlled, and the moisture absorption can be reduced without increasing the cost. The upper limit of the zinc content in 100% by mass of the phenolic resin for carbon materials is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, even more preferably 1.0% by mass or less, even more preferably 0.8% by mass or less, and even more preferably 0.5% by mass or less. By making the zinc content equal to or less than the upper limit, it is possible to provide a carbon material that can realize a lithium ion battery with improved discharge capacity.
[0053] <Resin composition> The resin composition of the present embodiment includes the phenolic resin for carbon materials and at least one selected from the group consisting of the negative electrode active material (B) and the precursor of the negative electrode active material (B). This can improve the discharge capacity of a lithium ion battery using the resin composition of the present embodiment. In this case, the above-mentioned components can be used as the negative electrode active material (B).
[0054] The precursor of the negative electrode active material (B) in the resin composition of this embodiment refers to a material that is converted into the negative electrode active material (B) by firing. Examples of the precursor of the negative electrode active material (B) include graphitizable or non-graphitizable materials such as petroleum pitch, coal pitch, and thermosetting resins, and thermosetting resins are preferred.
[0055] Examples of the thermosetting resin as a precursor of the negative electrode active material (B) include phenol resin, furan resin, epoxy resin, polyacrylonitrile, etc., and one or a mixture of two or more of them can be used. Among these, it is preferable to use a phenol resin, more preferably a resol type phenol resin or a novolac type phenol resin, and further preferably a novolac type phenol resin.
[0056] The resin composition of the present embodiment may also contain a curing agent. The curing agent used is not particularly limited, and for example, in the case of a novolac type phenolic resin, hexamethylenetetramine, a resol type phenolic resin, polyacetal, paraformaldehyde, etc. can be used. In addition, in the case of an epoxy resin, a curing agent known for epoxy resins can be used, such as a polyamine compound such as an aliphatic polyamine or an aromatic polyamine, an acid anhydride, an imidazole compound, dicyandiamide, a novolac type phenolic resin, a bisphenol type phenolic resin, or a resol type phenolic resin.
[0057] In addition to the above components, additives may be added to the resin composition. The additives used here are not particularly limited, but examples thereof include organic acids, inorganic acids, nitrogen-containing compounds, oxygen-containing compounds, aromatic compounds, non-ferrous metal elements, etc. These additives can be used alone or in combination of two or more depending on the type and properties of the resin used.
[0058] <Method of producing resin composition> The resin composition of the present embodiment can be obtained, for example, by mixing a phenolic resin for carbon materials with at least one selected from the group consisting of the negative electrode active material (B) and a precursor of the negative electrode active material (B). In this embodiment, the method of mixing the phenolic resin for carbon material with at least one selected from the group consisting of the negative electrode active material (B) and the precursor of the negative electrode active material (B) is preferably a mechanical kneader such as a kneader, a kneader, or a roll. Any mechanical kneader can be used as long as it can mix the phenolic resin for carbon material with at least one selected from the group consisting of the negative electrode active material (B) and the precursor of the negative electrode active material (B). In addition, premixing may be performed in advance, and there is no particular limitation on the method of premixing. For example, melt or solution mixing using a stirrer such as a homodisper or homogenizer; crushing and mixing using a crusher such as a centrifugal crusher, a free mill, or a jet mill; kneading and mixing using a mortar or pestle; etc. can be used. There is also no particular limitation on the order of mixing.
[0059] <Method of manufacturing composite materials> The method for producing the composite material of the present embodiment includes the steps of preparing a resin composition containing a phenolic resin for carbon material, and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B), and carbonizing the resin composition, thereby providing a composite material that can realize a lithium ion battery with improved discharge capacity.
[0060] (Step of preparing a resin composition containing a phenolic resin for a carbon material and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B)) First, a resin composition containing a phenolic resin for a carbon material and at least one selected from the group consisting of the negative electrode active material (B) and a precursor of the negative electrode active material (B) is prepared. The resin composition can be prepared by the methods described above.
[0061] (Step of carbonizing the resin composition) Next, the resin composition is carbonized. Through this process, the resin composition is converted into a carbon material, and when the resin composition contains a precursor of the negative electrode active material (B), the precursor of the negative electrode active material (B) is converted into the negative electrode active material (B).
[0062] The equipment for carbonizing the resin composition is not particularly limited, and any known equipment can be selected, such as a rotary kiln, a vertical shaft kiln, a batch-type heating furnace, a roller hearth kiln, a spray pyrolysis device, a spray dryer, etc. The above-mentioned equipment can be used alone or in combination of two or more types depending on the properties required for the carbon material (A) and the production efficiency of the carbon material (A).
[0063] The heating temperature when carbonizing the resin composition may be appropriately set within the range of preferably 400 to 1500° C., more preferably 450 to 1450° C., further preferably 500 to 1400° C., and further preferably 550 to 1300° C. The resin composition may be carbonized in a reducing atmosphere such as argon, nitrogen, or carbon dioxide.
[0064] In this embodiment, it is preferable to repeat the carbonization of the resin composition multiple times, which allows the physical properties of the resulting carbon material to be controlled. Furthermore, it is preferable to include at least one step of pulverizing the carbonized material obtained in the previous step between multiple carbonizations of the resin composition. Furthermore, the maximum carbonization temperature in the final carbonization of the above resin composition is preferably 400 to 1500°C, more preferably 600 to 1450°C, even more preferably 800 to 1400°C, and still more preferably 1000 to 1300°C.
[0065] In the present embodiment, the time for which the maximum carbonization temperature is maintained when carbonizing the resin composition (hereinafter referred to as the "maintenance time") is preferably 0 to 24 hours, more preferably 0 to 18 hours, even more preferably 0 to 12 hours, even more preferably 0.5 to 6 hours, even more preferably 1.0 to 4 hours, and even more preferably 1.5 to 2 hours, from the viewpoints of controlling the mechanical properties of the obtained carbon material (A) and improving the discharge capacity of a lithium ion battery using the obtained carbon material (A).
[0066] For example, when carbonizing the resin composition in two separate steps, the primary carbonization can be performed at a temperature of 150 to 700° C., and the carbon material can then be further treated at a temperature of 800° C. or higher (secondary carbonization).
[0067] <Lithium-ion battery anodes, lithium-ion batteries> Hereinafter, the negative electrode for a lithium ion battery and the lithium ion battery according to this embodiment will be described.
[0068] The negative electrode for a lithium ion battery according to this embodiment (hereinafter, sometimes simply referred to as a negative electrode) is manufactured using the carbon material according to this embodiment described above. This makes it possible to provide a negative electrode with excellent discharge capacity. The lithium ion battery according to this embodiment is manufactured using the negative electrode for lithium ion batteries according to this embodiment, and thus a lithium ion battery having excellent discharge capacity can be provided.
[0069] Hereinafter, preferred embodiments of the negative electrode for a lithium ion battery and the lithium ion battery according to the present embodiment will be described. FIG. 1 is a schematic diagram showing an example of a lithium ion battery according to this embodiment.
[0070] As shown in FIG. 1, the lithium ion battery 10 includes a negative electrode 13, a positive electrode 21, an electrolyte 16, and a separator 18.
[0071] As shown in FIG. 1, the negative electrode 13 has a negative electrode active material layer 12 and a negative electrode current collector 14. The negative electrode current collector 14 is not particularly limited, and a generally known negative electrode current collector can be used, such as copper foil or nickel foil.
[0072] The negative electrode active material layer 12 is preferably made of the composite material of this embodiment. The negative electrode 13 can be produced, for example, as follows.
[0073] To 100 parts by mass of the above composite material, 1 part by mass or more and 30 parts by mass or less of a commonly known organic polymer binder (for example, fluoropolymers such as polyvinylidene fluoride and polytetrafluoroethylene; rubber-like polymers such as styrene-butadiene rubber, butyl rubber, and butadiene rubber; etc.), 1 part by mass or more and 30 parts by mass or less of a conductive material (natural graphite, artificial graphite, expanded graphite, carbon black, acetylene black, carbon fiber, carbon tube, etc.), and an appropriate amount of a viscosity adjusting solvent (N-methyl-2-pyrrolidone, dimethylformamide, carboxymethylcellulose, etc.) or water are added and kneaded to prepare a negative electrode slurry. The obtained slurry is formed into a sheet or pellet shape by compression molding, roll molding, or the like to obtain the negative electrode active material layer 12. The negative electrode active material layer 12 thus obtained and the negative electrode current collector 14 are laminated to obtain the negative electrode 13. Moreover, the negative electrode 13 can also be produced by applying the obtained negative electrode slurry to the negative electrode current collector 14 and drying it.
[0074] The electrolyte 16 fills the space between the positive electrode 21 and the negative electrode 13, and is a layer through which lithium ions move upon charging and discharging.
[0075] The electrolytic solution 16 is not particularly limited, and a generally known electrolytic solution can be used. For example, a solution in which a lithium salt serving as an electrolyte is dissolved in a non-aqueous solvent can be used.
[0076] As the non-aqueous solvent, for example, cyclic esters such as propylene carbonate, ethylene carbonate, γ-butyrolactone, etc.; chain esters such as dimethyl carbonate, diethyl carbonate, etc.; chain ethers such as dimethoxyethane, etc.; or mixtures of these can be used.
[0077] The electrolyte is not particularly limited, and generally known electrolytes can be used, for example, lithium metal salts such as LiClO4, LiPF6, etc. Also, the above salts can be mixed with polyethylene oxide, polyacrylonitrile, etc., and used as a solid electrolyte.
[0078] There are no particular limitations on the separator 18, and any generally known separator can be used, such as a porous film of polyethylene, polypropylene, or the like, or a nonwoven fabric.
[0079] As shown in FIG. 1, the positive electrode 21 has a positive electrode active material layer 20 and a positive electrode current collector 22. The positive electrode active material layer 20 is not particularly limited and may be formed of a generally known positive electrode active material. The positive electrode active material is not particularly limited and may be, for example, a composite oxide such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or lithium manganese oxide (LiMn2O4); or a conductive polymer such as polyaniline or polypyrrole; or the like.
[0080] The positive electrode current collector 22 is not particularly limited, and a generally known positive electrode current collector, for example, aluminum foil, can be used. The positive electrode 21 in this embodiment can be manufactured by a generally known method for manufacturing a positive electrode.
[0081] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0082] The embodiments of the present invention will be described in detail based on Examples and Comparative Examples. It should be noted that the present invention is not limited to the Examples.
[0083] <Phenol resin> The following phenolic resins were used in the carbon materials of the examples and comparative examples.
[0084] Phenolic resin 1: High-ortho novolac type phenolic resin (manufactured by Sumitomo Bakelite Co., Ltd., product name: R-19H, ortho ratio: 69%, zinc content: 0.4% by mass)
[0085] Phenolic resin 2: Random novolac type phenolic resin (manufactured by Sumitomo Bakelite Co., Ltd., product name: PR-53195, ortho ratio: 41%, zinc content: 0% by mass)
[0086] <Carbonization of phenolic resin> The phenolic resins shown in Table 1 were placed in a batch-type heating furnace, and heated in a nitrogen atmosphere from room temperature at a heating rate of 100°C / hour. After reaching 550°C, the fired state was maintained for 1.5 hours to perform carbonization. After cooling, a pulverization process was carried out using a cyclone mill to obtain a carbon material precursor. Next, the carbon material precursor was placed in a batch-type heating furnace, and fired in a nitrogen atmosphere from room temperature at a heating rate of 100°C / hour to reach 1200°C. After that, the fired state was maintained for 2 hours to perform carbonization, and carbon materials of the examples and comparative examples containing phenolic resin carbonized materials were obtained.
[0087] <Evaluation> The physical properties of the carbon materials of the examples and comparative examples were evaluated by the following methods. The results are shown in Table 1.
[0088] (Orthogonal ratio (o-o' bond ratio)) The ortho conversion rate of each phenolic resin is 13 The amount of methylene groups bonded determined by C-NMR spectroscopy was substituted into the following formula (1) to calculate. Ortho ratio = (X+Y / 2) / (X+Y+Z) × 100(%) (1) X: Number of methylene groups bonded to the ortho-ortho positions of the phenol nucleus Y: The number of methylene groups bonded to the ortho- and para-positions of the phenol nucleus Z: Number of methylene groups bonded to the para-para positions of the phenol nucleus For the NMR measurements, a JNM-AL300 manufactured by JEOL Datum Co., Ltd. was used, and the measurement conditions were an accumulation number of 10,000.
[0089] (BET specific surface area) The BET specific surface area of the carbon materials obtained in the examples and comparative examples was measured by nitrogen adsorption method. Specifically, the carbon materials pre-dried at 100°C were placed in a glass cell and vacuum degassed at 350°C for 5 hours. Nitrogen gas was then introduced little by little at a temperature of 77K, and the equilibrium pressure and adsorption amount were measured. The measurement results were analyzed using the BET equation (equation (2) below) to determine the BET specific surface area (m 2 / g) were calculated respectively. P / V(P0-P)=1 / V m C+(C-1 / V m C)(P / P0) (2) Here, P is the adsorption equilibrium pressure, V is the amount of nitrogen gas adsorbed at the adsorption equilibrium pressure, P0 is the saturated vapor pressure, and V m indicates the amount of monolayer adsorption, and C indicates the heat of adsorption parameter.
[0090] (Peak intensity ratio) For the carbon materials of the examples and comparative examples, X-ray diffraction spectra were measured by X-ray diffraction (XRD) at a scanning speed of 1° / min using CuKα radiation as a radiation source, with 2θ on the horizontal axis and diffraction intensity on the vertical axis. In this X-ray diffraction spectrum, the peak intensities at 2θ values of 15°, 24°, and 35° were designated Ia, Ib, and Ic, respectively, and the peak intensity ratio was calculated as the peak intensity ratio = (Ia-Ic) / (Ib-Ic).
[0091] (true specific gravity) The carbon materials of the examples and comparative examples were dried at 135°C for 1 hour, and then the true specific gravity (g / cm) of the carbon materials of the examples and comparative examples was measured at room temperature using a dry automatic density meter Accupyc II 1340 (manufactured by Shimadzu Corporation). 3 ) was measured.
[0092] (moisture absorption rate) 1 g of the carbon materials of the examples and comparative examples was dried at 135° C. for 1 hour, and then left for 1 hour under conditions of temperature 40° C. / humidity 95% RH. The moisture absorption rate (%) was calculated from the change in mass of the carbon materials before and after leaving them, using the following formula (3). Moisture absorption rate (%) = (mass of carbon material after standing - mass of carbon material before standing) / (mass of carbon material before standing) x 100 (3)
[0093] (Raman spectroscopy, R value) One batch each of the carbon materials of the examples and the comparative examples was prepared, and measurements were performed under the following conditions using a Renishaw InViaReflex Raman microscope. At this time, measurements were performed at 16 points for one batch of carbon material, and a Raman spectrum was obtained each time. After baseline correction for each observed Raman spectrum, the peak at 1360 cm -1 Peak intensity near 1360 ) and 1580cm -1 Peak intensity near 1580 ) intensity ratio (R=I 1360 / I 1580 ) was calculated and the average value was calculated. Laser wavelength: 532nm Measurement range: 400cm -1 ~2000cm -1 Number of times: 4
[0094] (Carbonization yield) For the carbon materials of the examples and comparative examples, the mass before the above-mentioned <carbonization of phenolic resin> treatment was taken as the mass before carbonization, and the mass after the above-mentioned <carbonization of phenolic resin> treatment was taken as the mass after carbonization. The carbonization yield was evaluated by substituting the mass before carbonization and the mass after carbonization into the following formula (4). Carbonization yield (%) = {mass after carbonization / mass before carbonization} × 100 (4)
[0095] (Charge / discharge evaluation) To 100 parts by mass of the carbon material of each of the Examples and Comparative Examples, 1.5 parts by mass of carboxymethyl cellulose (CMC Daicel 2200, manufactured by Daicel Finechem), 3.0 parts by mass of styrene-butadiene rubber (TRD-2001, manufactured by JSR), 2.0 parts by mass of acetylene black (Denka Black, manufactured by Denki Kagaku Kogyo Co., Ltd.), and pure water were added in appropriate amounts, and the mixture was stirred and mixed using a rotation / revolution mixer to prepare a negative electrode slurry.
[0096] The prepared negative electrode slurry was applied to one side of a copper foil (manufactured by Furukawa Electric Co., Ltd., NC-WS) with a thickness of 14 μm, and then vacuum dried at 110° C. for 1 hour. After vacuum drying, an electrode was pressure-molded using a roll press. This was cut into a disk shape with a diameter of 13 mm to prepare a negative electrode. The thickness of the negative electrode active material layer was 50 μm.
[0097] The counter electrode was made of metallic lithium in the shape of a disk with a diameter of 12 mm and a thickness of 1 mm, and a polyolefin porous film (manufactured by Celgard, product name: Celgard 2400) was used as a separator.
[0098] Using the above negative electrode, counter electrode, and separator, and a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 3:7 to which LiPF6 was added at a ratio of 1M as the electrolyte, a bipolar half cell in the shape of a 2032 coin cell was manufactured in a glove box under an argon atmosphere.
[0099] The manufactured bipolar half-cell was charged and discharged under the following conditions. (Condition A) Measurement temperature: 25℃ Charging method: constant current constant voltage method, charging current: 25mA / g, charging voltage: 0mV, charging end current: 2.5mA / g Discharge method: constant current method, discharge current: 25mA / g, discharge end voltage: 2.5V (B condition) Measurement temperature: 25℃ Charging method: constant current constant voltage method, charging current: 40mA / g, charging voltage: 0mV, charging end current: 4.0mA / g Discharge method: constant current method, discharge current: 40mA / g, discharge end voltage: 1.5V
[0100] Based on the charge capacity and discharge capacity values obtained under the above conditions, the charge capacity and discharge capacity per gram of the negative electrode material [mAh / g] were calculated. The irreversible capacity and initial efficiency were calculated using the following formulas. Irreversible capacity [mAh / g] = (charging capacity) - (discharging capacity) Initial efficiency [%] = 100 × (discharge capacity) / (charge capacity)
[0101] [Table 1]
[0102] As shown in Table 1, it can be seen that the discharge capacity of the resulting lithium ion secondary battery was improved by using a carbonized phenolic resin having an ortho ratio of 50% or more as the negative electrode active material. [Explanation of symbols]
[0103] 10 Lithium-ion battery 12 Negative electrode active material layer 13 Negative electrode 14 Negative electrode current collector 16 Electrolyte 18 Separator 20 Cathode active material layer 21 Positive electrode 22 Positive electrode current collector
Claims
1. A carbon material (A) that can be used as a negative electrode active material for a lithium ion battery, The carbon material (A) contains a carbonized product of a phenolic resin having an ortho-conversion rate of 50% or more.
2. BET specific surface area is 0.1m 2 / g or more 50m 2 The carbon material according to claim 1, wherein the carbon content is 0.1 to 1.0 μm.
3. 3. The carbon material according to claim 1, wherein in an X-ray diffraction spectrum measured by an X-ray diffraction (XRD) method, a peak intensity ratio measured by the following method 1 is 0.90 or more and 1.25 or less. Method 1: In an X-ray diffraction spectrum obtained by measurement using CuKα radiation as a radiation source at a scanning speed of 1° / min, the horizontal axis represents 2θ and the vertical axis represents diffraction intensity, and the peak intensities at 2θ values of 15°, 24°, and 35° are designated as Ia, Ib, and Ic, respectively, to calculate the peak intensity ratio as (Ia-Ic) / (Ib-Ic).
4. True specific gravity is 1.50 g / cm 3 3.00g / cm or more 3 3. The carbon material according to claim 1 or 2, wherein:
5. 3. The carbon material according to claim 1, having a moisture absorption rate of 5.0% or more and 15.0% or less as measured by the following method 2. Method 2: 1 g of the carbon material is left for 1 hour under conditions of a temperature of 40° C. and a humidity of 95% RH. The moisture absorption rate (%) is calculated from the change in mass of the carbon material before and after being left standing using the following formula (3). Moisture absorption rate (%) = (mass of carbonaceous material after standing - mass of carbonaceous material before standing) / (mass of carbonaceous material before standing) x 100 (3)
6. The carbon material according to claim 1 or 2, wherein the R value in Raman spectroscopy measured by the following method 3 is 0.5 or more and 1.5 or less. Method 3: Using a micro Raman spectrometer, the Raman spectrum of the carbon material is measured under the following conditions. -1 The peak intensity (I 1360 ) and 1580 cm -1 The peak intensity (I 1580 ) intensity ratio (R value, R = I 1360 / I 1580 ) is calculated. Laser wavelength: 532 nm Measurement range: 400 cm -1 ~2000cm -1 ・Number of times: 4
7. A composite material comprising the carbon material (A) according to claim 1 or 2.
8. The composite material according to claim 7 , wherein the composite material comprises a negative electrode active material (B) different from the carbon material (A).
9. The composite material according to claim 8 , wherein the negative electrode active material (B) comprises a carbon material (B1) different from the carbon material (A).
10. The composite material according to claim 9, wherein the carbon material (B1) comprises one or more selected from the group consisting of graphite, hard carbon and soft carbon.
11. The composite material according to claim 8 , wherein the negative electrode active material (B) comprises one or more metal materials (B2) selected from the group consisting of metals and metal oxides.
12. The metal material (B2) is copper, gold, platinum, titanium, iron, cobalt, nickel, zinc, chromium, molybdenum, tungsten, palladium, calcium, strontium, barium, iridium, silver, cadmium, mercury, boron, aluminum, gallium, indium, thallium, silicon, tin, lead, antimony, bismuth and tellurium, and the composite material according to claim 11, which contains one or more selected from the group consisting of oxides thereof.
13. A phenolic resin for carbon materials capable of forming the carbon material according to claim 1 or 2, The phenolic resin for carbon materials has an ortho-conversion rate of 50% or more.
14. The phenolic resin for carbon materials according to claim 13, wherein the zinc content in 100% by mass of the phenolic resin for carbon materials is 0.1% by mass or more and 2.0% by mass or less.
15. The phenolic resin for carbon materials according to claim 13, wherein the phenolic resin for carbon materials comprises a thermoplastic phenolic resin.
16. The phenolic resin for carbon materials according to claim 15, wherein the thermoplastic phenolic resin comprises one or more selected from the group consisting of novolac-type phenolic resins and modified novolac-type phenolic resins.
17. A resin composition comprising the phenolic resin for a carbon material according to claim 13 and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B).
18. A step of preparing a resin composition containing the phenolic resin for a carbon material according to claim 13 and at least one selected from the group consisting of a negative electrode active material (B) and a precursor of the negative electrode active material (B); carbonizing the resin composition; A method for producing a composite material, comprising:
19. A negative electrode for a lithium ion battery, comprising the carbon material according to claim 1 or 2.
20. A lithium ion battery comprising the lithium ion battery negative electrode according to claim 19.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2002075357A